Role of pluralistic extension service providers in fisheries development of Rajasthan - Yadav, Rajpal; Sharma, Arpita; Maredia, Mywish; Sharma, Bhanu; Sharma, Laxmi (Journal of the Inland Fisheries Society of India, 2023)
Rajasthan has a vast amount of water resources but fish production is half of its potential. For fisheries development there are pluralistic extension service providers who undertake different schemes and programmes. Objective of this study was to documentroles of pluralistic extension service providers and prepare an inventory of all the schemes and programmes targeted towards fisheries development in Rajasthan by them. Information was collected from official websites and through discussions with the officials of respective organizations. The study revealed that there are multitude of diverse interventions, schemes and extension programmes undertaken by Central/State Government, NGOs and private organizations. Central Government programmes have a role towards inland fisheries development. State Government programs also have same role but focus on welfare programmes forfishers and tribal fishers. Role of NGOs is development of poor fishers and women groups. Private organizations are involved in the development of entrepreneurship in areas like ornamental fisheries, cage culture and saline aquaculture.